The measurement of air temperature in high speed flight - George, J. M. (College of Aeronautics, 1958)
The knowledge of air temperature has always been an. essential part of any flight test records for aircraft and engine performance calculations, and therefore the outside air thermometer is of vital importance. The majority of engine performance characteristics are presented as a function of the non-dimensional r.p.m. parameter and as, with the development of more advanced types of engines, the slopes of the characteristic curves are increasing, the accurate knowledge of both N and T4 is becoming steadily more important. This report is confined to the measurement of temperature, and Part I is devoted to sore theoretical considerations of the recovery factor on a flat plate and a cylinder with its axis parallel to the airstream. The effect of radiation has been taken into account and heat transfer expressions have been derived for laminar and turbulent boundary layers. The equilibrium temperature of a flat plate has also been evaluated over a range of airspeeds and altitudes assuming various amounts of radiation, and graphs have been included to show the deviation of the recovery factor with the variation of these two parameters. Part II contains an account of the preliminary testing of one of the temperature probes in the wind tunnel, and these tests were carried out with two main objects in view. The first was to ascertain the suitability of using thermistors as temperature sensing elements in outside air thermometers, and in particular to investigate their sensitivity and stability over a period of time. The second and prime object was to determine what effect a change of incidence would have on the recovery factor of a ventilated pitot thermometer probe... [cont.].